Malowana, glazurowana, polewana, siwa… Językowe i estetyczno-artystyczne wyróżniki ozdobnej ceramiki rzeszowskiej (na podstawie wybranych etnograficznych opracowań popularnonaukowych) - Węgorowska, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Decorative pottery and derived from it decorative ceramic are firmly interwoven with Polish folk culture. The article discusses linguistic and artistic distinguishing features of ceramic created in the Rzeszów region. It describes specialist vocabulary related to pottery and ceramic preserved in four popular science ethnographic studies (such as names of various kinds of ceramic, vessels, materials, thechniques, activities, performers of the activities, decorative motives and pottery centers). The characterized lexis permitted to reconstruct the facts connceted with the traditional handicraft representative of old and contemporary Subcarpathian heritage.
Keywords: ceramic; lexis; Rzeszów region; ethnography